Globalization and its Implications for the Field of Education in Indonesia: Between Challenge and Response - Subandowo, M; Suwirta, Andi (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: The process of globalization is now entering almost all aspects of human life. The process of globalization is due to the acceleration of innovation and its application in science and technology. All phenomena of globalization have had the implications in the field of education, including the education system in Indonesia. In the context of the teaching-learning process, for example, it seems to have been and will being changing, in pertaining with the development of science and information technology, that is emergencing of an e-learning phenomenon (learning through electronic media) and the application of multi-media technology in the learning process. Therefore, education in Indonesia must be ready to welcome the phenomena of globalization with all its challenges and responses. Indeed, the education sector in Indonesia is still a